Architecture, image and state: The architecture exhibition of the Ministry of Public Works of Uruguay in 1914 and its submission to the 1915 Panama-Pacific International Exposition - Medero, Santiago (Universidad ORT Uruguay, 2020)
The article proposes, through a particular case, to delve into the problem of the representation of the State through architecture at the beginning of the 20th century, when the foundations of modern Uruguay were still under construction. Through the review of an immediate antecedent, an exposition of the Ministry of Public Works in 1914 published in the Revista de la Asociación Politécnica del Uruguay, the work reflects on the Uruguayan shipment to the Panama-Pacific International Exposition of 1915, held at the city of San Francisco, in the United States. The buildings, represented through photographs and graphics, not only showed a desired modern Uruguay - highly literate, equipped and progressive - but also a conception of the architecture and construction of its capital, Montevideo, indebted to the concept of «monumentality». Under this conception, creator of «lay temples», architectural institutions and high politics found a common fund to operate.